The New Ecological Paradigm Scale from the Perspective of the Pre-Service Primary and Preschool Teachers' Ecological Narratives - Zorica P. Veinović; Јеlena M. Stanišić (University of Belgrade, Teacher Education Faculty, 2023)
The New Ecological Paradigm scale (NEP scale) examines the environmental view of the world and the results can be used for assessing the effectiveness of environmental education and planning future educational policies. Despite its widespread use, the scale is subject to criticism. In order to check the researchers' assumptions about the problematic nature of the statements in the scale, and encouraged by the broader context of the NEP scale application, we decided to conduct a qualitative research. The goal was to gain a better insight into the respondents' thoughts underlying their evaluations of the statements in the NEP scale. The sample consisted of the students of the Teacher Education Faculty, University of Belgrade. The NEP scale and the interview protocol were the instruments used in the research. The data were processed using the program for qualitative research MAXQDA 12. In the paper, we present a part of the results of a wider research. A comparative analysis of the responses in the scale and the respondents' narratives indicated a frequent discrepancy between these two categories of the responses in the 1st, 6th and 11th statements of the NEP scale. This called into question the possibility of using the NEP scale to determine the actual attitudes of the respondents regarding these claims. The analysis of the respondents' narratives identified the characteristics of the claims, which are the basis of the mentioned problems, and some of them include the absence of the environmental context, the vagueness of the parts of the specific claim, the complexity of the wording. These results suggest that, in order to gain a more objective insight into one's environmental worldview, it is necessary to revise the disputed claims in the scale or use it in combination with an interview.